STUDI ISLAM DALAM KAJIAN HUKUM KELUARGA ISLAM DI INDONESIA - sadari sadari (Indonesian Journal of Islamic Literature and Muslim Society, 2016)
This article offers a study of h}udu>di> (limit) in Islamic family law contained in the Indonesian Compilation of Islamic Law (KHI). The study of h}udu>di is nothing other than the process of desacralization that KHI becomes progressive in line with the development of modernity and in the context of Indonesian-ness. To that end, this article makes two efforts, firstly, by rejecting the idea that gives no attention to limit in one hand, and secondly, by strengthening the thoughts of scholars who offer new ijtihad both in its concept until to methodology. Thought that strengthens it came from Syrian figure, namely Muh}ammad Shah}ru>r, through a plausibility structure. His study of hudud supported Nurcholish Madjid idea about the de-sacralization, so as to perform the coherence between KHI to human rights issues, democracy, nation-state, civil society, and constitutionalism. So this article supports the spirit of de-sacralization - in addition to not abandon its sacralization - initiated by Nurcholish Madjid. The source of this study is KHI, by using the hudud paradigm, that based on a maxim of sabat al-nas wa harakah al-muhtawa, meaning that the text is permanent , but the content moves. So that the rule of law is always rooted in liminality based on the text, which is the pivot of study centered on the text toward the context, not vice versa.